2020
DOI: 10.3390/chemosensors8030060
|View full text |Cite
|
Sign up to set email alerts
|

Opto-Electronic Nose Coupled to a Silicon Micro Pre-Concentrator Device for Selective Sensing of Flavored Waters

Abstract: Headspace analysis of highly humid samples remains a challenge for artificial olfaction. Based on surface plasmon resonance imaging and bio-based sensors, the NeOse Pro olfactive analyzer yields multivariate data and enhances the statistical discrimination capacity of odor patterns. However, the presence of a high background signal, such as water vapor from aqueous samples, may deteriorate its discriminant ability. Recently, miniaturized pre-concentrators packed with hydrophobic adsorbent have been developed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Electronic noses are devices that also allow detection and identification of various volatile compounds or odors based on gas sensor arrays to simulate the function of the human olfactory system [ 6 ]. Concomitant with rapid developments in sensor technology, there is a plethora of electronic noses (e-noses) technologies that appeared lately [ 7 ], displaying different sensor chemistries [ 8 , 9 , 10 , 11 , 12 , 13 ]. As such, sensor arrays used in e-noses include many types of electrochemical sensors and different types of sensor-coating materials which are classified according to additive doping materials, the type and nature of the chemical interactions, the reversibility of the chemical reactions and running temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic noses are devices that also allow detection and identification of various volatile compounds or odors based on gas sensor arrays to simulate the function of the human olfactory system [ 6 ]. Concomitant with rapid developments in sensor technology, there is a plethora of electronic noses (e-noses) technologies that appeared lately [ 7 ], displaying different sensor chemistries [ 8 , 9 , 10 , 11 , 12 , 13 ]. As such, sensor arrays used in e-noses include many types of electrochemical sensors and different types of sensor-coating materials which are classified according to additive doping materials, the type and nature of the chemical interactions, the reversibility of the chemical reactions and running temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, IOMS possessed numerous advantages over sensorial (e.g., dynamic olfactometer) and analytical instrument (e.g., Gas chromatographymass spectrometry, colorimetric method, catalytic, infrared and electrochemical sensors, photoionization detector, differential optical absorption spectroscopy) because it is applicable for in-situ and in real time measurements [5][6][7][8]. Meanwhile, other techniques are Sensors 2021, 21, 114 2 of 16 combined with IOMS, such as pre-concentrator (i.e., silicon-micro), to improve the recognizing capability [9], Bluetooth to a smartphone for remote-controlling applications [4], and GC-MS to identify the responsible gas compounds in odour emission [10][11][12]. IOMS output odour metrics may include odour classification and/or odour quantification [13].…”
Section: Introductionmentioning
confidence: 99%
“…These systems were limited in terms of sensitivity and selectivity based on only one or few sensitive chemical layers. Since 2000, an increasing number of articles can be found in the literature using both biological and organic sensitive materials [185][186][187][188][189][190][191][192][193][194][195][196][197][198][199][200][201][202][203][204]. It has been demonstrated that SPR is very effective for sensing VOCs in the gas phase.…”
Section: Detection Of Vocs In Gas Phasementioning
confidence: 99%
“…NeOse Pro is a very promising tool for field analysis, although, as with most eNs, its use for the headspace analysis of highly humid samples remains a challenge, since its performance may be deteriorated by the presence of a high background signal generated by water vapor from aqueous samples. Slimani et al [189] have tackled this issue by using a miniaturized silicon preconcentrator packed with hydrophobic adsorbent coupled to the NeOse Pro (Figure 13). As a result, the eN showed not only a great improvement in the NeOse Pro is a very promising tool for field analysis, although, as with most eNs, its use for the headspace analysis of highly humid samples remains a challenge, since its performance may be deteriorated by the presence of a high background signal generated by water vapor from aqueous samples.…”
Section: Detection Of Vocs In Gas Phasementioning
confidence: 99%